2024
DOI: 10.1038/s41467-024-48374-2
|View full text |Cite
|
Sign up to set email alerts
|

Primacy of vision shapes behavioral strategies and neural substrates of spatial navigation in marmoset hippocampus

Diego B. Piza,
Benjamin W. Corrigan,
Roberto A. Gulli
et al.

Abstract: The role of the hippocampus in spatial navigation has been primarily studied in nocturnal mammals, such as rats, that lack many adaptations for daylight vision. Here we demonstrate that during 3D navigation, the common marmoset, a new world primate adapted to daylight, predominantly uses rapid head-gaze shifts for visual exploration while remaining stationary. During active locomotion marmosets stabilize the head, in contrast to rats that use low-velocity head movements to scan the environment as they locomote… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 169 publications
0
2
0
Order By: Relevance
“…We believe that the representation of scenes in these regions is provided by spatial view cells discovered in macaques in the hippocampus and parahippocampal cortex that respond to the part of the scene where a macaque is looking, and code for that in allocentric, world-based coordinates that are relatively independent of eye position, head direction, facing direction in the environment, and place where the individual is located (Rolls et al 1989 , 1998 , 1997 ; Rolls and O'Mara 1995 ; Robertson et al 1998 ; Georges-François et al 1999 ; Rolls 2023d , a ). Neurons with many similar properties that respond to locations “out there” being viewed in space have been reported in macaques and other primates by others (Wirth et al 2017 ; Mao et al 2021 ; Yang et al 2023 ; Zhu et al 2023 ; Piza et al 2024 ), and in humans (Ekstrom et al 2003 ; Tsitsiklis et al 2020 ; Donoghue et al 2023 ). In addition, some hippocampal neurons have been recorded in humans that respond during navigation towards the location of a particular goal in a virtual environment (Qasim et al 2019 ; Tsitsiklis et al 2020 ; Qasim et al 2021 ).…”
Section: Discussionmentioning
confidence: 63%
“…We believe that the representation of scenes in these regions is provided by spatial view cells discovered in macaques in the hippocampus and parahippocampal cortex that respond to the part of the scene where a macaque is looking, and code for that in allocentric, world-based coordinates that are relatively independent of eye position, head direction, facing direction in the environment, and place where the individual is located (Rolls et al 1989 , 1998 , 1997 ; Rolls and O'Mara 1995 ; Robertson et al 1998 ; Georges-François et al 1999 ; Rolls 2023d , a ). Neurons with many similar properties that respond to locations “out there” being viewed in space have been reported in macaques and other primates by others (Wirth et al 2017 ; Mao et al 2021 ; Yang et al 2023 ; Zhu et al 2023 ; Piza et al 2024 ), and in humans (Ekstrom et al 2003 ; Tsitsiklis et al 2020 ; Donoghue et al 2023 ). In addition, some hippocampal neurons have been recorded in humans that respond during navigation towards the location of a particular goal in a virtual environment (Qasim et al 2019 ; Tsitsiklis et al 2020 ; Qasim et al 2021 ).…”
Section: Discussionmentioning
confidence: 63%
“…In contrast, in primates the predominant spatial representation in the hippocampus and parahippocampal cortex is provided by spatial view neurons that code for the location ‘out there’ where the primate or human is looking in space [ 1 , 2 , [40] , [41] , [42] , [43] , [44] ]. This discovery is supported by much recent evidence from primates [ [45] , [46] , [47] , [48] , [49] ] and humans [ [50] , [51] , [52] ]. Thus these AI-based studies do not address what is found in the hippocampus of humans and other primates, or the generation of a whole memory from any part in the human hippocampal memory system.…”
Section: Ai-based Approaches To Understanding Hippocampal Memory Func...mentioning
confidence: 58%
“…In contrast, in primates the predominant spatial representation in the hippocampus and parahippocampal cortex is provided by spatial view neurons that code for the location ‘out there’ where the primate or human is looking in space [ 1 , 2 , [40] , [41] , [42] , [43] , [44] ]. This discovery, together with much recent evidence from primates [ [45] , [46] , [47] , [48] , [49] ] and humans [ [50] , [51] , [52] ] (see the Special Issue of Hippocampus, May 2023), is leading to a revolution in our understanding of hippocampal function in primates including humans, in that this allows memories to be formed of where people and objects are in spatial scenes even though the viewer may never have visited the places being viewed. This is prototypical of human memory, and means that hippocampo-neocortical function as we now understand it is highly relevant to understanding human generative memory brain systems [ 1 , 2 , 40 ].…”
Section: Generative Ai Compared To the Generation By The Human Hippoc...mentioning
confidence: 99%